(untitled) (Journal of Mechanical Engineering, 2013)
For development to be sustainable, it should be able to meet the needs of the present withoutcompromising the ability of future generations to meet their own needs. Generally, development is consideredunsustainable when insufficient attention is paid to the economic, environmental and social consequences. Aprerequisite for development is growth and that is directly related to production or output of a country. Ifproduction is done via a sustainable path it can maintain the sustainability of development. Mechanical andManufacturing Engineers predominantly shoulder manufacturing. As mechanical engineering is somewhatconsidered the merging ground of all forms of engineering, the level of mechanical engineering can be areliable barometer for measuring the development in a country. Thus mechanical engineers play a vital role indevelopment in countries across the globe. This paper highlights the role, responsibilities and necessarycontributions required by mechanical engineers to achieve sustainable development in time. DOI: http://dx.doi.org/10.3329/jme.v42i1.15911